The screening of blood by Aspergillus PCR and galactomannan ELISA precedes BAL detection in patients with proven and probable IA - Springer, Jan; Loeffler, Juergen; Einsele, Hermann; White, P. Lewis (Medical Mycology, 2021)
Early detection of Aspergillus infection has the potential to facilitate a more effective management of invasive disease. Data from probable/proven cases of invasive aspergillosis (IA) with a positive galactomannan enzyme-linked immunosorbent assay (GM) bronchoalveolar lavage fluid (BALF) was analyzed in respect to serum GM and/or polymerase chain reaction (PCR) screening of blood samples prior to, or concurrent with bronchoscopy. Concurrent serum GM testing is less sensitive than BALF itself. Nevertheless screening of blood using GM or PCR testing detected IA cases earlier (GM: 42% or PCR: 56%), particularly when combined (GM/PCR: 73%). Therefore, regular screening facilitates and improves early detection of IA in patients suffering from acute leukemia.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Aspergillus; Blood; Bronchoalveolar lavage; Galactomannan ELISA; PCR screening